Secondary Structure Preferences of Mn2+ Binding Sites in Bacterial Proteins. (17th March 2014) - Khrustaleva, Tatyana Aleksandrovna
Abstract : 3D structures of proteins with coordinated Mn 2+ ions from bacteria with low, average, and high genomic GC-content have been analyzed (149 PDB files were used). Major Mn 2+ binders are aspartic acid (6.82% of Asp residues), histidine (14.76% of His residues), and glutamic acid (3.51% of Glu residues). We found out that the motif of secondary structure "beta strand-major binder-random coil" is overrepresented around all the three major Mn 2+ binders. That motif may be followed by either alpha helix or beta strand. Beta strands near Mn 2+ binding residues should be stable because they are enriched by such beta formers as valine and isoleucine, as well as by specific combinations of hydrophobic and hydrophilic amino acid residues characteristic to beta sheet. In the group of proteins from GC-rich bacteria glutamic acid residues situated in alpha helices frequently coordinate Mn 2+ ions, probably, because of the decrease of Lys usage under the influence of mutational GC-pressure. On the other hand, the percentage of Mn 2+ sites with at least one amino acid in the "beta strand-major binder-random coil" motif of secondary structure (77.88%) does not depend on genomic GC-content.